Seguridad vial, accidentes y responsabilidad empresarial en Lima: Revisión sistemática 2019-2024 - Santivañez Sanchez , José Luis (2025)
The high rate of traffic accidents is one of the main ongoing problems in Peruvian society, resulting in the loss of lives and material damage to vehicles or public infrastructure. In response to this situation, laws and regulations have been enacted to regulate vehicle traffic in Peru. The aim of this study is to conduct a literature review on road safety, traffic accidents, and corporate responsibility. Using a qualitative methodology, the hypothetical-deductive method and documentary technique were applied to gather information from reliable research sources. It concluded that the State has the constitutional duty to guarantee road safety through the planning, execution, and supervision of public infrastructure, as well as the implementation of comprehensive prevention policies. The administrative authority exercises powers of regulation, oversight, and sanction, which must be carried out in harmony with the protection of fundamental rights.